Millennials: el nuevo reto del marketing - Rivera, Cecilia; Canacas, Ingrid Berenice; Jovel, Delmy Elena; Romero, Jacqueline Andrea (Realidad Empresarial, 2017)
No hay resúmenes disponibles. Realidad Empresarial No. 3, 2017: 7-13